Educational Inequality and Social Mobility in Karnali Province of Nepal: A Sociological Analysis - Neupane, Krishna Prasad (Karnali Outlook: Knowledge Across Disciplines, 2026)
This article examines how educational inequality shapes social mobility in Nepal, with particular attention to Karnali Province. The study used a descriptive and analytical design based on secondary data from the Central Bureau of Statistics, EMIS, provincial education reports, and publications of agencies such as UNESCO, UNICEF, and UNDP. Key indicators include literacy, enrolment and retention, access to secondary and higher education, and disparities by gender, caste, and province. Sociological theories of stratification and mobility guide the interpretation of these patterns and help explain how structural conditions influence people’s life chances. The findings showed that Karnali consistently lags behind the national average in literacy, school retention, educational expenditure, and access to higher education, and it records one of the lowest intergenerational mobility scores in the country. Girls, Dalit communities, and children from poor households face particularly high risks of dropout and exclusion from advanced schooling. These gaps are reinforced by geographic isolation, weak institutional capacity, and persistent socio-cultural barriers. Educational inequality in Karnali therefore appears not only as a statistical difference but as a major obstacle to upward mobility and local development. The study argues that narrowing these provincial gaps is essential for promoting fair social mobility in Nepal. It calls for targeted policies that improve resources, strengthen provincial and local institutions, and prioritize inclusive measures for marginalized groups in Karnali.